Coupled effects of chlorides and sulfates on steel reinforcement corrosion in concrete structures: A comprehensive review - Ye Tian; Yu Liu; Yu-Meng Xie; Guo-Yi Zhang; Hai-Long Ye; Dong-Ming Yan; Yun-Jian Li; Bei Li; Hong-Jing Xue; Qing Cai (Case Studies in Construction Materials)
Steel reinforcement corrosion is the main reason for the decrease in the durability of concrete structures, and concrete structures serving in the coupled environment of chloride and sulfate are prone to steel reinforcement corrosion. Therefore, it is necessary to explore the coupled effect of chloride and sulfate on concrete degradation and steel corrosion. This paper provides a comprehensive review of the corrosion of steel reinforcement in concrete structures exposed to coupled invasion of chlorides and sulfates. The natural exposure stations and tests of concrete under chloride and sulfate attack around the world are discussed. The complex interactions and coupled transport models involved in the erosion process of chloride and sulfate ions are explained. From the perspectives of the direct effect of chloride ions on steel corrosion and the influence of sulfate ions on chloride-induced steel corrosion, the mechanism of steel corrosion in a coupled environment of chlorides and sulfates is represented. The paper also summarizes relevant experimental research and numerical simulation research. It emphasizes the importance of further research to clarify the direct mechanism of sulfate ions on the passive film on the steel surface and their reactions in the electrochemical corrosion process. Comprehensive consideration and accurate simulation of the factors influencing steel corrosion are crucial for advancing the prediction of the durability of reinforced concrete structures.